Ammonius Lithotomos (3rd Century BC), the Alexandrian Innovative Surgeon Who Introduced Lithoclastic Cystotomy. (April 2017) - Tsoucalas, Gregory; Sgantzos, Markos
Alexandrian surgeon Ammonius Lithotomos, was the first to introduce lithoclastic cystotomy during the 3rd century BC in order to relieve a bladder's stone blockage. He had used a metallic hook or crotchet to remove the stone, which was named at the era "thrombus" of the urinary tract.